Ricucire pratiche e narrazioni migranti. Per un fare materico e trasformativo - Paini, Anna; Maltese, Stefano; Varvarica , Sabaudin (Antropologia Pubblica, 2024)
Starting from the experience of the Research Project Mending distances, reconnecting places: sharing everyday life (RiCu, 2019-2021) aimed at promoting forms of coexistence and mutual acknowledgement between asylum seekers and local communities, we reflect on the political, ethical and operational dimensions that the Third Mission can assume when knowledge and anthropological practices overstep the academic context to interact with the local one. By considering the relevance and complexity of doing-together, we therefore propose an itinerary of Third Mission where the canonical dimensions of the dissemination of research interplay with more transformative perspectives and practices.